DOCTRINE OF TRANSPORTATION SECURITY IN THE CONTEXT OF THE MODERN STATE FORMATION - Bezzubov, Dmytro (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
However the provision of the proper level of transportation security is one of the main tasks of the modern state. Nowadays this is confirmed by the attention paid to the security matters in the developed countries, including transportation, and is the subject to the significant importance of transportation development for any modern country. Notwithstanding the necessity of integration into European and world community, Ukraine is doomed to pay much attention to transportation security. Besides it should be mentioned that Ukraine has the highest transit rating in the Europe. Accordingly it can get significant income due to the transit and provision of other transportation services only if the robust transportation security system is built. This also stipulates the importance of transportation security matters for Ukraine. TheconditionofthetransportationsecurityinUkraineisinsufficientin comparison to the other developed countries worldwide. Primarily it is subject to the automobile and railway transportation being the main source of the threats in the transportation security sphere. Taking into account the requirements of the European Union regarding the Association Agreement in the field of security it is necessary to prioritize the innovations in the field [2]. Thus nowadays namely the provision of all types of security is the propriety task among all its other types worldwide. Accordingly it is the level of the transportation security to be the one of the main indexes of the transportation security level in the country. The doctrine of the transportation security laysin the formation of the unified normative, technical, methodological and systemapproachestotheprovision of the security while using all transportation types. The development and implementation of this doctrine is possible while constantly improving the normative base, forming the technical requirements to the transportation vehicles. Herewith the doctrine of transportation security covers the ecological, air, space, economic and administrative legal categories.